Gender Trends in Mortality in the Irkutsk Region - Ya. A. Leshchenko (Scientific Сentre for Family Health and Human Reproduction Problems, 2020)
Background. A hypothesis on the main role of factors of psychosocial and psychological distress in the formation of gender differences in mortality in the post-Soviet period is proposed. Aim of the research. To identify the characteristics and main causes of changes in gender trends and indicators of sexual dimorphism in mortality of the population of the Irkutsk region in the post-Soviet period. Methods. Statistical materials were obtained from the databases of the Federal State Statistic Service of the Russian Federation and from the Demographic Yearbooks of Russia. To establish the gender characteristics of irrevocable demographic losses, we analyzed the values of the male excess mortality index. It is defined as the ratio of the mortality rate of men to the corresponding indicator for women. We established the close connection between changes in the male supermortality index and the level of psychological distress of the population. The last index was determined by the suicide rate. Results. During the 31-year period (1987–2017), the highest values of the male mortality index were observed in 1993– 1995 and in 2001–2005. An indicator of the frequency of suicides is proposed and applied as a specific socio-demographic criterion for the influence of the factor of psychological distress on the socio-demographic status of the population. The dependence of the male supermortality index on the level of psychological distress for the period from 1991 to 2017 is estimated. A strong positive relationship between these indicators was identified (r = 0.792; p < 0.0001). Conclusion. Changes in the indicator of male supermortality largely depend on changes in the level of psychological distress. The indicator of sexual dimorphism of mortality (the index of male supermortality) can be used as an important indicator of pronounced changes in psychosocial and psychological distress and, accordingly, the quality of life of a society.